“Incluencia de los factores biodemográficos maternos en la asfixia neonatal en parto vaginal en el hospital de apoyo San José Callao” - Pineda López, Evila (1995)
During the period of August of 1,989 1,994 July is attended in the Hospital "San José" support from the city of Callao, 7 maternity service 039, newborns alive of whom 535 (7.60%) were discharged with a diagnosis of neonatal asphyxia, which constituted our study material. Biodemograficos maternal risk factors were analyzed and complied in every one of them in two groups: LOW RISK and HIGH RISK. Results were statistically significant for maternal age (p < 0.001), marital status (p < 0.10), occupation (p < 0.001), origin (p < 0.001), parity (p < 0.001), birth period (p < 0.001), gestational age (p < 0.001), antenatal care (p < 0.001), except for the degree of instruction (p < 0. 10). In conclusion demonstrated is the relationship between factors high risk maternal biodemograficos and neonatal asphyxia.